Unilateral phrenic nerve stimulation for neurogenic hypoventilation in Arnold Chiari malformation - Nitin Garg (Indian Journal of Neurosurgery)
Long- term ventilator dependence in patients with neurogenic hypoventilation is associated with significant morbidity and restricts mobility. Diaphragmatic pacing by phrenic nerve stimulation (PNS) is a viable alternative. This is a case report of patient with Arnold-Chiari malformation with extensive syrinx who had neurogenic hypoventilation during sleep even after foramen magnum decompression and resolution of the syrinx. Unilateral PNS was done using spinal cord stimulator. With intermittent stimulation for 8 h while asleep, patient could be weaned off the ventilator completely. At 2 years follow- up, patient is ambulant and has returned to his routine activities. PNS is a good treatment tool in patients with neurogenic hypoventilation. Spinal cord stimulator can be used with optimal results. This is first such reported case of using spinal cord stimulator for PNS from India.